Expression of 85‐kDa Protein of Adriamycin‐resistant Tumor Cells during Hematopoietic Differentiation of THP‐1 and HEL Cells - Ishii, Shigetaka (Jpn J Cancer Res, 1992)
An 85‐kDa protein was identified in adriamycin‐resistant tumor cells recognized by monoclonal antibody MRK‐20. Recently, the monoclonal antibody MRK‐20 was found to be reactive to human peripheral mononuclear cells. In order to investigate the molecular function of the 85‐kDa protein, we carried out flow cytometric analysis of the expression of the 85‐kDa protein during monocytic differentiation of the hematopoietic cells. Human myelomonocytic leukemia THP‐1 cells were induced to differentiate into macrophage‐like cells by treatment with 12‐O‐tetradecanoylphorbol‐13‐acetate (TPA), A maximum of 55% of the cells expressed the 85‐kDa protein along with the CD‐14 antigen, which is a surface marker of monocytes and macrophages. The kinetic analysis revealed that the 85‐kDa protein appeared prior to the expression of the CD‐14 antigen. The 85‐kDa protein was also coexpressed with CD‐14 in THP‐1 cells that were induced to differentiate by recombinant tumor necrosis factor‐a, which is one of the physiological inducers of monocytic differentiation. In human erythroleukemia, HEL cells, the 85‐kDa protein was constitutively coexpressed with CD‐14. The expression of both the 85‐kDa protein and CD‐14 was drastically reduced during the megakaryocytic differentiation of the HEL cells with TPA. These results suggest that the 85‐kDa protein could be expressed on monocytic cells as well as CD‐14 and that the expression of the 85‐kDa protein might be regulated at an earlier stage of monocytic differentiation of hematopoietic cells than the expression of CD‐14.